The Types of Flouting Maxim Found In Alice In Wonderland Movie - Ni Made Verayanti Utami; Ni Nyoman Deni Ariyaningsih; Ida Ayu Popy Wulandari Pratiwi (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2021)
This study entitled The Types of Flouting Maxim found in Alice in Wonderland movie. The study aimed to find out the types of flouting maxim used by characters. This study focused on Grice (1975) about the types of flouting maxim. This study applied the descriptive qualitative method in analyzing the data. To get valid data, this study used note-taking as a technique. The findings showed that there are 4 types of flouting maxim used by the characters. The result of the study showed that the types of flouting maxim found in the movie are 25 data. The dominant flouting maxim uttered by the characters in this movie is the flouting maxim of relevance with the frequency 10 (40%). The findings shows that the most dominant flouting maxim used by the characters is the flouting maxim of relevance because the characters in this movie try to hide the main character's existence by changing the topic in the conversation. Keywords: flouting maxim, types, movie